Los cambios en el control de mando en las firmas según la teoría de agencia: una hipótesis para explicar el surgimiento del Sindicato Antioqueño (2019)
This paper reviews the main aspects of the agency theory, and emphasizes on the positivist line, which shows strengths in explaining the birth of the Sindicato Antioqueño or the Grupo Empresarial Antioqueño (GEA), recognized as one of the largest Colombian economic groups. The main conclusion is that the managers’ interests as well as those of a group of shareholders where the ones pursued, and that in the process, cross ownership between the companies were established. This article is a result of the research “Characterization of the Sindicato Antioqueños´s Head Quarters”.